Doom - Bartkowiak, Andrzej, 1950-; Urban, Karl, 1972-; Pike, Rosamund, 1979-; Oparei, DeObia; Daniels, Ben, 1964-; Adoti, Razaaq; Pierce-Roberts, Tony.; Mansell, Clint; Universal Pictures (Firm) (Universal City, CA : Universal Pictures, 2006)
Something has gone terribly wrong at a remote scientific research station on Mars. All research at the station has ceased and communication with Earth is failing. The messages that do get through are becoming more frantic and less than comforting. It's a level 5 quarantine and the only humans allowed in or out of the area are the Rapid Response Tactical Squad - hardened Space Marines armed to the teeth with enough firepower to destroy a legion of nightmarish creatures.
Title from container.
Based on the video game 'Doom.'
Originally released as a motion picture in 2005.
Special features: First-person shooter sequence; "Game on!": a beginner's tour of locations, weapons, creatures and strategies; "Basic training": join The Rock and the rest of the cast as they train with the SAS; "'Doom' nation": exploring the worldwide phenomenon of 'Doom' the video game franchise.
Director of photography, Tony Pierce-Roberts ; editors, Derek Brechin, Peter Dansie, Chris Lloyd, Toby Lloyd ; music, Clint Mansell ; costume designer, Carlo Poggioli ; production designer, Stephen Scott ; visual effects supervisor, John Farhat.
Karl Urban, Rosamund Pike, DeObia Oparei, Ben Daniels, Raz Adoti, Richard Brake, Al Wesver, Dexter Fletcher, Brian Steele, The Rock.
Keywords: Doom (Computer file) -- Fiction; Mercenary troops -- Drama; Human-alien encounters -- Drama; Mars (Planet) -- Exploration -- Drama; Feature films; Films for the hearing impaired; Science fiction -- Feature; Thriller -- Feature